2014
DOI: 10.1371/journal.pone.0102653
|View full text |Cite
|
Sign up to set email alerts
|

Association between Polymorphisms in the TSHR Gene and Graves' Orbitopathy

Abstract: BackgroundGraves' orbitopathy (GO) as well as Graves' disease (GD) hyperthyroidism originate from an autoimmune reaction against the common auto-antigen, thyroid-stimulating hormone receptor (TSHR). GO phenotype is associated with environmental risk factors, mainly nicotinism, as well as genetic risk factors which initiate an immunologic reaction. In some patients GO is observed before diagnosis of GD hyperthyroidism, while it can also be observed far after diagnosis. The intensity of GO symptoms varies greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 51 publications
0
14
1
Order By: Relevance
“…A series of reports have been confirming that the inheritance of AA genotype for TSHR rs179247 increases the risk for GD [29,30,47,48]. However, contradicting our results, Lui et al [47] suggested that the A allele in rs179247 was highly increased in Chinese patients with GO only, whereas Jurecka-Lubieniecka et al [49] demonstrated that younger patients without GO, in whom GD was diagnosed before 30 years of age, the A allele was more frequent. In this study, the presence of AA genotype was associated with a significant reduction in the risk of GO.…”
Section: Discussioncontrasting
confidence: 85%
“…A series of reports have been confirming that the inheritance of AA genotype for TSHR rs179247 increases the risk for GD [29,30,47,48]. However, contradicting our results, Lui et al [47] suggested that the A allele in rs179247 was highly increased in Chinese patients with GO only, whereas Jurecka-Lubieniecka et al [49] demonstrated that younger patients without GO, in whom GD was diagnosed before 30 years of age, the A allele was more frequent. In this study, the presence of AA genotype was associated with a significant reduction in the risk of GO.…”
Section: Discussioncontrasting
confidence: 85%
“…Additionally, 1 study did not have sufficient data, and 28 studies did not study the three SNPs. In the end, we selected 8 studies that met the inclusion criteria, including 5 studies that involved 4821 GD patients and 4846 healthy controls 12 19 20 21 22 and 5 studies that involved 904 GO patients and 924 GD patients 20 22 23 24 25 . Importantly, the study by Ploski included 3 different groups of cases and controls 12 .…”
Section: Resultsmentioning
confidence: 99%
“…About 25–50 % of these patients develop Graves’ orbitopathy that might lead to irreversible ocular changes resulting in disturbed vision, changed facial appearance, and a significantly decreased quality of life [ 20 ]. The pathogenesis of Graves’ orbitopathy is unresolved so far, and many distinct factors are postulated to be involved (endogenous, genetic, environmental) [ 21 – 23 ]. Recently published study suggested the association between Graves’ orbitopathy prevalence and severity and diabetes mellitus type 2 with accompanying overweight [ 24 ].…”
Section: Introductionmentioning
confidence: 99%